Green innovation and competition: R&D incentives in a circular economy - Giovanna Bimonte; Maria Grazia Romano; Maria Russolillo (Games, 2021)
The present paper provides theoretical insights regarding the determinants of firms' incentives to invest in a Circular Economy. The analysis relies on a Cournot model disaggregating the disposal cost in the production function. In a non-simultaneous sequential game, two risk-neutral firms are endowed with a green innovation project that, if successful, would reduce the overall production costs and implement a Circular Economy. Firms are plagued by asymmetric information about the exact value of the other firm's innovation. In this setting, the R&D investment in a Circular Economy, by affecting the distribution of production and disposal costs, influences the production decisions of both the innovating and the rival firms. The sign of the impact depends on the firms' strategy in the product market. Furthermore, the analysis points out that cooperation in R&D of firms competing in the product market reinforces incentives to invest in green innovation. This suggests that governments aimed to advance a Circular Economy should encourage firms' cooperation.
Keywords: 330; circular economy; cournot oligopoly; green innovation; R&D investment spillovers